Likelihood ratios and the strength of statistical evidence - Blume, Jeffrey (Henry Stewart Talks, 2007)
Using likelihood ratios to measure the strength of statistical evidence in data, Paradigms for measuring statistical evidence: the three questions, Likelihood ratios, The law of likelihood, The likelihood principle, Misleading evidence, Probabilities of observing misleading evidence and their bounds, Sequential designs in the likelihood paradigm, Composite hypothesis and extensions, Example using real data from a well known clinical trial
Reviewed at 2017/09/28